Novel biosynthesis of silver nanoparticles using Ulva lactuca and their potential toward environment and agricultural purposes - Taibi, Mariame; Aouji, Marouane; Imtara, Hamada; Abujaber, Feras; Oubihi, Asmaa; Ouannou, Abdelmalek; Hajji, Lhoussain; Shahat, Abdelaaty A.; Noman, Omar M.; Tarayrah, Mahmoud; Bengueddour, Rachid; Hassani, Oussama (Frontiers in Sustainable Food Systems, 2024)
In the global field of nanotechnology, the production of silver nanoparticles is an environmentally beneficial technique. In order to prevent the diseases that most of the pesticides that were once in use caused, we now need to synthesis safe pesticides from low-cost sources. The eco-friendly extracellular production of silver nanoparticles from a solution of silver nitrate using Ulva lactuca aqueous extract as a reducing agent. The biosynthetic reaction has been demonstrated by the use of UV-VIS, FT-IR, SEM and EDAX. Moreover, antioxidant activity was confirmed. It has also been evaluated against a variety of bacteria and fungi that have an impact on humans, animals, and plants. The mean size of the particles varied from 45 to 61 nm. The disc diffusion testing results show that, in comparison to the tested antibiotics, Staphylococcus aureus, Escherichia coli, Staphylococcus epidermidis and Klebsiella pneumoniae were more responsive to Ulva lactuca-silver nanoparticles (U-AgNPs) extract. Teldor 50%sc fungicide was used at the prescribed dose of 0.5 µL/mL, and the antifungal activity of aqueous and U-AgNPs extracts was examined at three concentrations of 0.62, 1.25, and 2.5 mg/mL. Through the suppression of spore germination, in vitro investigations demonstrated that U-AgNPs at varying doses greatly hindered the process of reproductive growth of Botrytis cinerea. Comparing U-AgNPs to the standard synthetic fungicide Teldor 50% sc, it's noteworthy to observe that a substantial control efficacy against tomato and strawberry gray mold was noticed, especially at concentrations of 2. mg/mL on the entire tomato and strawberry plants and also on the detached leaves and fruits without causing any appearance damage. In summary, this study advances the field of agro-nanotechnology by demonstrating the potential application of a fungicide based on nanoparticles to prevent gray mold on tomato and strawberry plants in greenhouse environments and throughout the postharvest phase.